The venezuelan migratory phenomenon and the charges registered to the SEAT from 2019 to 2021 - Parra Meneses, Erika Johanna
This article seeks to analyze The migratory Venezuelan phenomenon between 2019 and 2021 in Colombia, based on the information recorded in the different databases provided by the control entities with which it seeks to monitor the different variables that may affect the national health system and its users in various areas of its application. Objective: To analyze the information that allows to get relevant data of the Venezuelan population, which affects the SOAT for outpatient services. Methodology: For the purposes of this article we made a database research, which allows us to identify variables and patterns towardsoutpatient care to Venezuelan migrants for injuries in traffic accidents charged to the SOAT. Result: To determine billed services to the insurance companies for traffic accidents where there is one or more victims identified as Venezuelan migrants. Conclusion: To establish and detail the processing of information in the management of economic resources from the payment of the premium established in order to generate the coverage to the services provided to the affected Venezuelan victims, so they will be taken into account from 2019, before the beginning of the COVID-19 pandemic, and the year 2020 during the beginning of the COVID-19 pandemic, this being important due to the affectations caused for the management of the sanitary emergency decreed by the national government and the year 2021 post-pandemic for COVID-19 as a starting point for the economic reactivation in Colombia.